Integrated Continuous Bioprocess Development for ACE-Inhibitory Peptide Production by Lactobacillus helveticus Strains in Membrane Bioreactor - Raveschot, Cyril; Deracinois, Barbara; Bertrand, Emmeline; Flahaut, Christophe; Frémont, Marc; Drider, Djamel; Dhulster, Pascal; Cudennec, Benoit; Coutte, François (Frontiers in Bioengineering and Biotechnology, 2020)
Production of bioactive peptides by Lactobacillus species is a cost-effective approach compared to the use of purified enzymes. In this study, proteolytic Lactobacillus helveticus strains were used for milk fermentation to produce bioactive peptides capable of inhibiting angiotensin converting enzyme (ACE). Fermented milks were produced in bioreactors using batch mode, and the resulting products showed significant ACE-inhibitory activities. However, the benefits of fermentation in terms of peptide composition and ACE-inhibitory activity were noticeably reduced when the samples (fermented milks and non-fermented controls) were subject to simulated gastrointestinal digestion (GID). Introducing an ultrafiltration step after fermentation allowed to prevent this effect of GID and restored the effect of fermentation. Furthermore, an integrated continuous process for peptide production was developed which led to a 3 fold increased peptide productivity compared to batch production. Using a membrane bioreactor allowed to generate and purify in a single step, an active ingredient for ACE inhibition.